Utilização de compostos orgânicos associados a adubação mineral e extrato de algas no meloeiro - Alves Júnior, Antônio Roberto (Universidade Federal Rural do Semi-Árido, 2021)
The melon cultivation is constantly expanding in the Northeast semi-arid, given its high added value and adaptation to the region's edaphoclimatic conditions. Improving fertilizer management techniques has fundamental importance to optimizing the use of fertilizers. The organic fertilizers use and biostimulants along with mineral fertilizers in this crop has an innovative character and can be more efficient in providing nutrients. In order to evaluate the organic fertilizer effect and algae extract in the mineral fertilizer presence used by the producer on the soil chemical characteristics, yield and fruit quality, an experiment was conducted in a commercial production area in the rural county of Mossoró-RN, from September to November 2019. The experiment was conducted with Pele de Sapo melon, Grand Prix hybrid, in a randomized block experimental design, in a split-plot design [(2x2)+2]x3, with two types of organic compounds and two doses of each organic compound, added of two controls, combined with three sources of biostimulant, all with 6 repetitions. The treatments in the plots had the following composition: absolute control (without fertilization); relative control (0.08 kg/m of mineral fertilizer in formulation 6-24-12); bovine compost + mineral fertilizer (2.0 kg/m + 0.08 kg/m); bovine compost + mineral fertilizer (1.0 kg/m + 0.08 kg/m); poultry compost + mineral fertilizer (1.0 kg/m + 0.08 kg/m) and poultry compost + mineral fertilizer (0.5 kg/m + 0.08 kg/m). For the subplots, the treatments were defined as: control (without biostimulant); Martello seaweed extract (1L/ha) and Acadian seaweed extract (1L/ha). The characteristics evaluated were: yield, longitudinal and transverse diameter, peel and pulp thickness, pulp firmness, soluble solids, titratable acidity, soluble solids/titratable acidity ratio (SS/TA) and soil nutrient contents at the cycle end. It was observed that there was no significant effect among the 18 treatments in post-harvest, except when there were splits showing that within the mineral fertilization the Martello extract implied higher productivity and longitudinal diameter, and that in relation to doses of poultry compost, the lowest dose resulted in greater shell thickness. Furthermore, evaluating the treatments only as a function of the application of extracts, both contributed to a greater transverse diameter. Regarding the soil chemical attributes, the mineral and bovine compost combination promoted a greater increase in Ca2+ in relation to the control. For Mg2+, sum of bases and effective CTC, the best increments came from the use of mineral fertilizer and the mineral combination with organic poultry compost. All soils that received fertilization promoted a higher total CTC. With the cultivation and addition of treatments, there was an increase in pH and available phosphorus, and a reduction in soil potassium contents
Keywords: Cucumis Melo; Manejo; Bioestimulante; Cucumis Melo; Management; Biostimulant; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO